Designing and manufacturing of the extremely low frequency electromagnetic field generator and detector - Rezaei-Tavirani, Mostafa; Rostami, Amin (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Electromagnetic fields (EMFs) are inevitable consequences of modern civilizations and the era of technology. Many investigations have been carried out in order to determine the effects of EMFs on biological organisms specially on human being. In one hand, most of the generators used in these kinds of experiment are not able to expose a large number of animals simultaneously and on the other hand, many environmental electromagnetic fields could be hazardous for exposing people while a portable, low cost and reliable electromagnetic detector is not commercially available. In this study, we introduced an ELF/EMFs generator capable of exposing a large experimental space and a detector of environmental ELF/EMFs which can define their spatial parameters and relevant biological effects.